Morphometric Study of Hippocampal CA1 Pyramidal Neurons after Tualang Honey Administration - Mohd Yusoff, N.L.; Kamarulzaidi, Mohd Amiruddin; Tiong, Sheena Yin Xin; Hasan Adli, Durriyyah Sharifah (Microscopy Society of Malaysia, 2018)
Tualang honey can be collected from the hives of Apis dorsata bee species on Tualang trees. Its various nutritional and curative properties could probably be due to its antioxidant effects. Subsequent to previous studies demonstrating its positive effects on spatial memory performance and hippocampal neuronal count, the current study investigated whether it has morphometric effects on the hippocampal cornu ammonis 1 (CA1) pyramidal neurons. It is important to evaluate the characteristics of hippocampal constituent neurons since this brain structure, which is primarily involved in memory processing, is most vulnerable towards oxidative stress. Male Sprague Dawley rats were force-fed five days a week for 12 consecutive weeks with 1.0ml/100g body weight of 70% Tualang honey (HON) or with 0.9% saline (SAL) as control. Nissl’s stained dorsal transverse hippocampal sections (8µm thick) of both groups were visualized under Olympus BX51 light microscope. Images were captured using Analyzer Life Science software and morphometric analysis was conducted using Image-Pro Premier 9.1 64-bit software. Only neuronal somas with clear nucleus and nucleolus were included in the morphometric analysis. Significant differences were observed between the groups for all five parameters selected (somatic area [SA], somatic perimeter [SP], somatic aspect ratio [SAR], somatic circularity index [SCI], and somatic roundness [SRo]). Values of SA and SP of HON group indicated significantly bigger sized CA1 neurons. Values of SAR, SCI and SRo, which indicated the shape of the neuronal somas, are biased towards less rounded shape. These values demonstrated HON has effects at the neuronal morphometric level.